PENYELENGGARAAN MAKANAN DAN TINGKAT KEPUASAN KONSUMEN DI KANTIN ZEA MAYS INSTITUT PERTANIAN BOGOR - Arnati Wulansari; Budi Setiawan; Tiurma Sinaga (Jurnal Gizi dan Pangan, 2013)
This research aimed was to know food service and level of customer satisfaction in the Zea Mays cafetaria at Bogor Agricultural University. Case study and descriptive analysis were applied in this study. Sampling method of purposive sampling was carried out and number of subjects used was 95 people. The food service in the Zea Mays cafetaria consists of planning, purchasing, receiving, storing, processing, and distributing. The result of analysis based on Importance Performance Analysis showed that the most important attribute was the security and hygiene product and the highest performance levels was the cleanliness of dining room. More than fifty percent subjects was concerned against nutrient content of the menu (50.5%). Based on the Customer Satisfaction Index the satisfaction value was 69.3 (satisfied). There was a correlation between job and education level with quality of the product and between income with nutrient content (p<0.05).